The greening of golf Sport, globalization and the environment - Millington, Brad (Globalizing Sport Studies, 2016)
Golf is a major global industry. It is played by more than 60 million people worldwide, and there are more than 32,000 courses across the globe in 140 countries. This book looks at the power relationships in and around golf, examining whether the industry has demonstrated sufficient leadership on environmental matters for the government to be able to trust them to make decisions with implications for public health. It is the first comprehensive study of the varying impacts of golf on the environment, and is based on extensive empirical research, including interviews with major stakeholders in the golf industry and members of protest groups. The authors examine golf as a sport and as a global industry, drawing on three discrete literatures - the study of sport as a global social movement, environmental sociology and the study of corporate environmentalism.